An evaluation of the strengthening of national behavior through developing and training of national non-commissioned officers of West Papua regional police - Simangunsong, Junus; Purnomo, Langgeng (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
The development of